Fiqh Education in Pesantren as a Model for Fiqh Education in the World - Syahputra, Ali (The Institute of Research and Service Community IPMAFA Pati, 2023)
The community considers that fiqh in pesantren is lagging, so it cannot answer the issues that are rampant in the current era. Most of them consider that fiqh is an instant and final legal product that does not need to be reinterpreted several times. The attempt to provide a re-understanding of the fiqh of the past has experienced a deadlock because of the strong position of fiqh in the minds of Muslims. What Fazlur Rahman experienced until the tragedy of Nasr Hamid Abu Zayd is a small part of the evidence. This study aims to analyze and examine fiqh in pesantren as a model of fiqh education in the world. This research uses qualitative methods with data collection techniques through participant observation, in-depth interviews, and documentation analysis. This study found that the classical fiqh books (kitab kuning) in pesantren are not only legal products that cannot be reinterpreted but also discuss worship. However, classical fiqh can be used as a model of fiqh education in the world. The research is expected to be taken into consideration so that fiqh education in pesantren can be used as fiqh education in the world.